2022
DOI: 10.3390/plants11070981
|View full text |Cite
|
Sign up to set email alerts
|

Using Consensus Land Cover Data to Model Global Invasive Tree Species Distributions

Abstract: Invasive tree species threaten ecosystems, natural resources, and managed land worldwide. Land cover has been widely used as an environmental variable for predicting global invasive tree species distributions. Recent studies have shown that consensus land cover data can be an effective tool for species distribution modelling. In this paper, consensus land cover data were used as prediction variables to predict the distribution of the 11 most aggressive invasive tree species globally. We found that consensus la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It was also observed that the 11 IPS mainly distributed in tropical rainforests and grasslands, subtropical evergreen broad-leaved forests, and the Mediterranean region (Figure 2). These climate regions have abundant species resources, sufficient rain, heat, and forest resources [77]. Biodiversity is also richer in places with abundant plant resources [77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also observed that the 11 IPS mainly distributed in tropical rainforests and grasslands, subtropical evergreen broad-leaved forests, and the Mediterranean region (Figure 2). These climate regions have abundant species resources, sufficient rain, heat, and forest resources [77]. Biodiversity is also richer in places with abundant plant resources [77].…”
Section: Discussionmentioning
confidence: 99%
“…These climate regions have abundant species resources, sufficient rain, heat, and forest resources [77]. Biodiversity is also richer in places with abundant plant resources [77]. For example, the invasive Morella faya is highly scattered throughout a narrow distribution area [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we can use the results of modeling to develop actionable recommendations for biological conservation and risk prevention and control [4][5][6]. Despite their important uses, there are still many technical issues involved with the use of SDMs [7,8]. Addressing these issues will greatly improve the forecasting accuracy of SDMs, improve the feasibility of environmental management/policymaking, and create a bridge between modelers and decision-makers.…”
Section: Introductionmentioning
confidence: 99%